2008
DOI: 10.1007/s00384-008-0612-z
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal manometry with reference to operative rectal biopsy for the diagnosis/exclusion of Hirschprung’s disease in children under 1 year of age

Abstract: In children under 1 year of age, Hirschprung's disease is very unlikely in the presence of a RAIR. The specificity and positive predictive value of ARM for the diagnosis of Hirschprung's disease are inferior to those of rectal suction biopsy, and therefore, it cannot be recommended for use as a sole diagnostic tool for this disease. ARM may be a useful investigation in patients where the histologic specimen is inadequate and/or functional constipation is the most likely diagnosis. If RAIR is present, rectal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, the reported diagnostic accuracy of ARM versus RSB varies considerably, and ARM has been reported to have a significantly lower rate of specificity and positive predictive value in some studies. 53,54 Additionally, the accuracy of ARM in the diagnosis of HSCR in neonates conflicts in the literature. [55][56][57] In a subgroup analysis of diagnostic accuracy of ARM in infants younger than 6 months, de Lorijn et al 41 found overall lower sensitivity of 88% and specificity of 89% but no significant difference from the total group.…”
Section: Anorectal Manometrymentioning
confidence: 99%
“…However, the reported diagnostic accuracy of ARM versus RSB varies considerably, and ARM has been reported to have a significantly lower rate of specificity and positive predictive value in some studies. 53,54 Additionally, the accuracy of ARM in the diagnosis of HSCR in neonates conflicts in the literature. [55][56][57] In a subgroup analysis of diagnostic accuracy of ARM in infants younger than 6 months, de Lorijn et al 41 found overall lower sensitivity of 88% and specificity of 89% but no significant difference from the total group.…”
Section: Anorectal Manometrymentioning
confidence: 99%
“…ARM has the advantages of being a less-invasive method without the exposure to ionizing radiation. The limitations include the need for the patient to be in a normal physiologic and quiet state to avoid possible artefacts (35,36). A recent comprehensive systematic review by de Lorijn et al (35) compared the diagnostic accuracy among RSB, ARM, and BE for the diagnosis of HD.…”
Section: Armmentioning
confidence: 99%
“…26 At anorectal manometry, the physiological recto-anal inhibitory reflex induced by rectal distension, is absent. 28 The diagnosis should be confirmed by the absence of ganglia and the abundance of cholinergic nerve fibers in the rectal biopsy performed at least 2 cm above the dentate line to avoid the physiologic aganglionic zone in the caudal rectum. 29 Most cases of Hirschsprung's disease are sporadic and are associated with mutations in the receptor tyrosine kinase proto-oncogene.…”
Section: Is E a S E S A Sso Ciated With Cip Omentioning
confidence: 98%